The effects of probiotics, prebiotics, and synbiotics on polycystic ovarian syndrome: an overview of systematic reviews - Angoorani, Pooneh; Ejtahed, Hanieh-Sadat; Ettehad Marvasti, Fateme; Taghavi, MinaSadat; Mohammadpour Ahranjani, Behzad; Hasani-Ranjbar, Shirin; Larijani, Bagher (Frontiers in Medicine, 2023)
Accumulating evidence has highlighted a critical role of the gut microbiota and its potential action as a regulator of metabolic disorders including insulin resistance, obesity and systemic inflammation in polycystic ovarian syndrome (PCOS). Microbiota-modulating interventions such as probiotics, prebiotics and synbiotics could be effective in PCOS management. We conducted an overview of systematic reviews (SRs) and meta-analyses to summarize reviews regarding the effectiveness of pro-/synbiotics on management of PCOS through a systematic literature search in PubMed, Web of Science, and Scopus databases until September 2021. Eight SRs and meta-analyses were included in this study. Our overview confirmed that probiotics supplementation had a potentially beneficial effect on some PCOS related parameters including body mass index (BMI), fasting plasma glucose (FPG) and lipid profiles. Evidence shows that synbiotics in comparison with probiotics were less effective on these parameters. The methodological quality of SRs was assessed using the AMSTAR-2 assessment tool and were determined as high for four SRs, low for two SRs and critically low for one SR. Due to limited evidence and high heterogeneity of the studies, it remains difficult to identify optimal probiotics strains, prebiotics types, length of duration and doses. Future clinical trials with higher quality are recommended to clarify the efficacy of pro-/pre-/synbiotics on management of PCOS and provide more accurate evidence.